Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Development of a Stereolithography 3D Printing-Based Micropatterning Method to Study Endothelial-to-Mesenchymal Transition Mechanobiology - Karina Bender; Sarah Chesley; Jay Lesny Drake; Megan Ho; Emily Lin; Kathryn Saxton; Ninava Sharma; Christina K. Tripsas; Qian Li; Jeffrey J. Hsu (Annals of Biomedical Engineering, 2026)
Endothelial-to-mesenchymal transition (EndMT) is the process of endothelial cells undergoing molecular changes that shift their phenotype from that of endothelial cells to that of mesenchymal-like cells. It is a crucial developmental process that has been implicated in various physiological and pathological conditions. EndMT has gained attention as a potential therapeutic target for cardiovascular disease processes, including atherosclerosis, myocardial fibrosis, and vascular calcification. In addition to the assessment of endothelial and mesenchymal markers, the behavioral mechanics of endothelial cells, such as migration and invasion, are often used to identify endothelial cells that have undergone EndMT. However, whether cell chirality may be another mechanobiological marker of EndMT remains unclear. In this study, we aimed to develop an accessible micropatterning platform and created a stereolithography (SLA) 3D printing-based polydimethylsiloxane (PDMS) protein-stamp fabrication platform to create customized patterns of ECM proteins to study endothelial cell chirality during EndMT. Human aortic endothelial cells (HAECs) were treated with the inflammatory cytokine tumor necrosis factor-α (TNF-α), which resulted in the downregulation of the endothelial marker ENOS3 and the upregulation of the mesenchymal markers N-cadherin and transgelin, supporting the induction of EndMT. HAECs were seeded onto fibronectin stripe micropatterns, and cell chirality was measured using custom cell-profiling software. HAECs treated with TNF-α exhibited a shift in cell orientation by approximately 18°, supporting altered cell chirality during TNF-α-induced EndMT. Our work innovates novel methods of studying EndMT by developing a flexible and cost-effective protein-stamp fabrication and image analysis pipeline. This pipeline can be used by researchers to study the endothelial cell chirality in response to EndMT induction.

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

The different adsorption-degradation behaviors of SARS-CoV-2 by bioactive chemicals in wastewater: The suppression kinetics and their implications for wastewater-based epidemiology - Mohamed Bayati; Hsin-Yeh Hsieh; Shu-Yu Hsu; Sally Qasim; Chenhui Li; Anthony Belenchia; Jessica Klutts; Sally A. Zemmer; Kristen Sibley; Melissa Reynolds; Elizabeth Semkiw; Hwei-Yiing Johnson; et al. (Science of The Total Environment, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

Correction to: Long-Term Oral Toxicity and Anti-osteoporotic Effect of Sintered Dicalcium Pyrophosphate in Rat Model of Postmenopausal Osteoporosis - Yuh-Feng Tsai; Li-Ho Hsu; Chang-Chin Wu; Wei-Hua Cai; Kai-Chiang Yang; Fang-Yu Fan (Journal of Medical and Biological Engineering, 2020)

Long-Term Oral Toxicity and Anti-osteoporotic Effect of Sintered Dicalcium Pyrophosphate in Rat Model of Postmenopausal Osteoporosis - Yuh-Feng Tsai; Li-Ho Hsu; Chang-Chin Wu; Wei-Hua Cai; Kai-Chiang Yang; Fang-Yu Fan (Journal of Medical and Biological Engineering, 2017)
Sintered dicalcium pyrophosphate (SDCP), a synthetic pyrophosphate analog, has shown potential for the management of osteoporosis. The long-term oral toxicity and anti-osteoporotic effect of SDCP in a postmenopausal osteoporosis rat model were evaluated in this study. SDCP was orally administered to bilateral ovariectomized (OVX) Wistar rats at a dose of 0.75 mg/kg daily for 24 weeks following by 2 weeks of observation. There were no abnormal findings in clinical signs of toxicity, food consumption, body weight, blood examination, necropsy, and histological inspection attributable to the ingestion of SDCP. The serum level of type I collagen fragments, a bone resorption marker, decreased in SDCP-treated rats, and the bone formation markers alkaline phosphatase, osteocalcin, and osteopontin significantly decreased. These findings indicate that the bone turnover rate decreased in SDCP-treated animals. Relative to OVX rats, the increase in serum tartrate-resistant acid phosphatase 5b level represents an increase in bony tissues in the SDCP-treated rats. Histological examinations of distal femoral metaphyses further revealed that the ingestion of SDCP improved the trabecular bone architecture and decreased bone porosity. Analysis of limb bone ashes showed a significant increase in bone mineral content. Our results show that SDCP inhibits bone resorption to restore bone mass in OVX rats without deleterious effects, and therefore that SDCP has potential in the management of osteoporosis.

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Enhanced Therapeutic Epidermal Growth Factor Receptor (EGFR) Antibody Delivery via Pulsed Ultrasound with Targeting Microbubbles for Glioma Treatment - Ai-Ho Liao; Hsin-Yi Chou; Yi-Lei Hsieh; Sheng-Chieh Hsu; Kuo-Chen Wei; Hao-Li Liu (Journal of Medical and Biological Engineering, 2015)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)